2004
DOI: 10.1158/1078-0432.ccr-04-0208
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Fhit Expression in Head and Neck Squamous Cell Carcinoma and Its Potential Clinical Implication

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
1
19
0
3
Order By: Relevance
“…A tumor suppressor role for FHIT was postulated based on the ability of FHIT to eliminate or reduce the tumorigenicity of tumor cells in nude and knockout mice (34,35) and is now widely accepted (6). Several reports showed previously that loss of heterozygosity occurs frequently at the chromosome region containing FHIT (4,5,36) and that the expression of FHIT is frequently altered in head and neck SCC (11,19,21,37,38) and POLs (6,22,39).…”
Section: Discussionmentioning
confidence: 99%
“…A tumor suppressor role for FHIT was postulated based on the ability of FHIT to eliminate or reduce the tumorigenicity of tumor cells in nude and knockout mice (34,35) and is now widely accepted (6). Several reports showed previously that loss of heterozygosity occurs frequently at the chromosome region containing FHIT (4,5,36) and that the expression of FHIT is frequently altered in head and neck SCC (11,19,21,37,38) and POLs (6,22,39).…”
Section: Discussionmentioning
confidence: 99%
“…17 The tumor suppressor gene fragile histidine triad (FHIT) spans the FRA3B fragile site, 18 and abnormal FHIT transcription and low FHIT expression were detected in various human cancers, including oral squamous cell carcinomas. 19,20 Studies of the two most frequently affected common fragile site loci, FRA3B and FRA16D, have provided compelling evidence that these regions are indeed prone to DNA instability in cancer cells. 21 It has also been shown that exposure to environmental carcinogens such as smoking and alcohol consumption increases the potential for chromosome breakage at fragile sites FRA3B and FRA16D in esophageal, non-small-cell lung and cutaneous squamous cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the risk of distant metastasis is higher, but not statistically significant, yet as loco regional recurrence is cross-referenced, it was found to be rare in patients with FHIT expression loss. It has been argued that in patients with FHIT expression loss, sensitivity to radiotherapy is higher, hence loco regional recurrence is lower [22]. It has thus been concluded that the tumors in patients with decreasing FHIT expression are radiosensitive.…”
Section: Discussionmentioning
confidence: 99%